Pola Asuh dalam Pemenuhan Hak Anak Pada Masa Pandemi Covid-19 di Lembaga Panti Asuhan Dahlan Syafi’i - Subkhiya, Fajriatis (LoroNG: Media Pengkajian Sosial Budaya, 2021)
Children are the next generation of the nation that must be maintained health and fulfillment of their rights. Each parent, teacher, government, and community is responsible for the growth and development of children such as physical, knowledge, psychological, and social. This study aims to determine the pattern of parenting in the fulfillment of children’s rights during the COVID-19 pandemic at the Dahlan Syafi’i orphanage. The research method uses a qualitative approach, data collection methods through in-depth interviews, observation, and documentation. The subjects or informants in this study were the caretakers of the orphanage and 2 Dahlan Syafi’i orphans. The results showed (1) the types of parenting applied by the caregivers were authoritarian, authoritative, and permissive. (2) Fulfillment of children’s rights during the pandemic include (a) Guaranteeing children’s health and growth and development, (b) Assisting and educating during online learning, (c) Delivering information as a provision of children’s knowledge, (d) Establishing massive communication and cohesiveness, (e) Meet with biological parents, (f) Set a good example. Anak merupakan generasi penerus bangsa yang harus dijaga kesehatan dan pemenuhan haknya. Masing-masing orang tua, guru, pemerintah, dan masyarakat bertanggungjawab atas tumbuh kembang anak seperti fisik, pengetahuan, psikis, dan sosial. Penelitian ini bertujuan untuk mengetahui pola asuh dalam pemenuhan hak anak di masa pandemi Covid-19 di lembaga panti asuhan Dahlan Syafi’i. Metode penelitian menggunakan pendekatan kualitatif, metode pengumpulan data melalui wawancara mendalam, observasi dan dokumentasi. Subjek atau informan dalam penelitian ini adalah pengasuh panti asuhan dan 2 anak yatim piatu Dahlan Syafi’i. Hasil penelitian menunjukkan (1) jenis pola asuh yang diterapkan oleh pengasuh adalah authoritarian, authoritative dan permissive. (2) Pemenuhan hak anak di masa pandemi diantaranya (a) Menjamin kesehatan dan tumbuh kembang anak, (b) Mendampingi dan mendidik selama pembelajaran daring, (c) Menyampaikan informasi sebagai bekal pengetahuan anak, (d) Menjalin komunikasi dan kekompakan secara masif, (e) Bertemu dengan orang tua kandung, (f) Memberi teladan yang baik.